2013
DOI: 10.1186/1471-2121-14-41
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid has different effects on UCP1 expression in mouse and human adipocytes

Abstract: BackgroundIncreased adipose thermogenesis is being considered as a strategy aimed at preventing or reversing obesity. Thus, regulation of the uncoupling protein 1 (UCP1) gene in human adipocytes is of significant interest. Retinoic acid (RA), the carboxylic acid form of vitamin A, displays agonist activity toward several nuclear hormone receptors, including RA receptors (RARs) and peroxisome proliferator-activated receptor δ (PPARδ). Moreover, RA is a potent positive regulator of UCP1 expression in mouse adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 63 publications
2
53
0
Order By: Relevance
“…Oil Red O staining and immunoblotting for hormone-sensitive lipase (HSL) confirmed the robust differentiation using the protocol employed (Supplementary Fig. 1), in congruence with our previous reports 29,30 . Based on the in vivo expression levels and cold-induced changes (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Oil Red O staining and immunoblotting for hormone-sensitive lipase (HSL) confirmed the robust differentiation using the protocol employed (Supplementary Fig. 1), in congruence with our previous reports 29,30 . Based on the in vivo expression levels and cold-induced changes (Fig.…”
Section: Resultssupporting
confidence: 89%
“…1). The gene expression changes were consistent with previously published data confi rming that SGBS preadipocyte differentiation is a reproducible model for the study of human adipogenesis ( 12,(37)(38)(39)(40).…”
Section: Lipid-quant Data Analysis and Outputsupporting
confidence: 80%
“…Retinoic acid administration in vivo increases UCP1 mRNA and protein expression in WAT depots in mice [250,251], which is associated with antiobesity and antidiabetic effects in vivo [251]. Retinoic acid administration to cultured adipocytes (3T3-L1 adipocytes, C3H10T1/2 adipocytes, or MEFs) during differentiation also increases UCP1 mRNA expression [250,251], through a p38 MAPK-mediated mechanism [252] that is independent of PGC-1␣ [253]. While both of these studies agree that activation of RAR is involved, as the increase in UCP1 mRNA can be achieved with the RAR agonist TTNPB [250,251], Mercader et al were also able to increase UCP1 mRNA expression with the RXR agonist methoprene [252], although Berry et al found no effect with the RXR-specific agonist 9cis-retinoic acid [251].…”
Section: Retinoidsmentioning
confidence: 99%